Kepemimpinan Politik Menurut Raja Ali Haji - Fazira (UIN Syarif Hidayatullah Jakarta), Gilang (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2024)
This study aims to analyze Raja Ali Haji’s views on political leadership. The recent rise in immoral, corrupt, and selfish leaders highlights the urgent need for reform. This serves as a reminder for us to choose leaders who meet the criteria of ideal leadership, in order to create a happy and prosperous society in line with the values and goals of Islamic teachings. As a scholar, thinker, and statesman, Raja Ali Haji developed a concept of political leadership rooted in Islamic tradition and Malay culture, which remains relevant in certain aspects to the current context. This research uses a descriptive-analytical method. It is a library research based on Raja Ali Haji’s primary work Tsamarat al-Muhimmah, supported by secondary sources such as books, journals, articles, and other scholarly works related to leadership. The thesis writing technique follows the Rector’s Decree No. 507 and the 2017 UIN Jakarta Guidelines for Scientific Writing. This study shows that a leader should be someone respected by the community, as such a leader would nurture the people, possess high moral standards, protect them from harm, provide guidance, and lead them in both worldly and spiritual matters. Such a leader is knowledgeable and firmly upholds Islamic teachings. Leaders with these qualities are believed to be capable of fostering both physical and spiritual well-being.